Materialistic values and goals. [article]. - Kasser, Tim
Materialism comprises a set of values and goals focused on wealth possessions, image, and status. These aims are fundamental aspect of the human value/goal system, standing in relative conflict with aims concerning the well-being of others, as well as one's own personal and spiritual growth. Substantial evidence shows that people who place a relatively high priority on materialistic values/goals consume more products and incur more debt, have lower-quality interpersonal relationships, act in more ecologically destructive ways, have adverse work and educational motivation, and report lower personal and physical well-being. Experimentally activating materialistic aims causes similar outcomes. Given these ills, researchers have investigated means of decreasing people's materialism. Successful interventions encourage intrinsic/self-transcendent values/goals, increase felt personal security, and/or block materialistic messages from the environment. These interventions would likely be more effective if policies were also adopted that diminished contemporary culture's focus on consumption, profit, and economic growth. -- (from the author)